Influence of bleaching agents on the microhardness of nanoparticle resin composite - Vanderlei Salvador Bagnato; Marcelo Ferrarezi de Andrade; Alessandra Nara de Souza RASTELLI; Simone Xavier Silva Costa; Anne Buss BECKER; Carlos Alexandre Souza Bier (Faculdade São Leopoldo Mandic, 2009)
Objective: To assess the effect of bleaching agents on the microhardness of nanoparticle resin composite. Methods: Twenty-eight cylindrical test specimens (8x1mm) of FiltekTM Supreme XT resin (3M/ESPE) were prepared and divided into 5 groups. The initial Vickers microhardness was measured (load of 50 grams force for 30 seconds) on the top surface of the test specimens. The groupswere treated and divided as follows: G1 - artificial saliva (21 days - control); G2 - 7% hydrogen peroxide gel applied for 4h/day, for 14 days; G3 - 10% carbamide peroxide for 4h/day, for 14 days: G4 - 35% hydrogen peroxide gel applied in three sessions of 30 minutes each, with an interval of one week (21 days) between the sessions; G5 - 35% carbamide peroxide, three sessions of 30 minutes each, with an interval of one week (21 days) between the sessions. The top surfaces of the test specimens received treatment and were submitted to the Vickers microhardness test. Results: The results obtained were submitted to the Analysis of Variance at a fixed criterion, at a level of significance of p=0.05. No significant differences were observed among the treatments tested (p=0.42) when compared with G1. Significant differences (Tukey test) were found when the initial microhardness values were compared with the values after experimental treatments (p<0.01). Conclusion: The application of bleaching agents did not alter the microhardness of resin composites. Therefore, there is no need to change restorations after bleaching.